EVALUASI DAN ANALISIS POSTUR KERJA PADA PEKERJA PABRIK KELAPA SAWIT PT. X - Chindy Revadi; Christoper Davin; Yemima K Ginting (JURNAL MANAJEMEN REKAYASA DAN INOVASI BISNIS, 2023)
To increase productivity, companies at this time are required to reduce the problem of musculoskeletal disorders. Musculoskeletal disorder is a complaint experienced by a worker on the musculoskeletal part that affects the movement of the body or human skeletal muscle system due to non-ergonomic work postures. To reduce musculoskeletal disorders, it is necessary to evaluate work posture analysis using the Standard Nordic Questionnaire, Rapid Upper Limb Assessment, and Rapid Entire Body Assessment. The results of the evaluation and analysis can provide recommendations for improvement to reduce the level of risk of discomfort and work accidents.